Beetles (Insecta: Coleoptera) as bioindicators of the assessment of environmental pollution. Issue 2 (17th February 2018) - Ghannem, Samir; Touaylia, Samir; Boumaiza, Moncef
ABSTRACT: Bioindicators have been generating great interest in environmental pollution research. Insects and especially arthropod are useful to assess the effects of anthropogenic activities on the terrestrial ecosystem, because they are inclose contact with toxic elements present in soil and in leaf litter. Beetles are extremely sensitive to several ecological parameters, react quickly to environmental modifications and can be easily and cost-effectively sampled by various methods. These criteria make beetles excellent indicators of terrestrial ecosystem. In order to evaluate the environmental impact of human activities on different ecosystems, the use of Coleoptera in ecological studies has been largely increased in recent years. This review presents the results obtained by researchers when using beetles as bioindicators of metallic pollution and forest disturbance.